Antimicrobial susceptibility patterns of Acinetobacter baumanii isolates from ICU and non-ICU wards - Budayanti, Ni Nyoman Sri; Suranadi, I Wayan; Tarini, Made Adi; Violentina, Gusti Ayu Dianti; Sathya Deva, I Dewa Gde (Bali Journal of Anesthesiology, 2019)
ABSTRACTIntroduction: Acinetobacter baumanii is the most common agent of hospital-acquired infection with the increasing fatality rate due to multidrug-resistant (MDR) strain infection. The magnitude of the problem in Indonesia is unknown. Here, we provide data regarding susceptibility pattern of A. baumanii isolated from a tertiary referral hospital in Bali, Indonesia between 2012 and 2014.Methods: Data were collected retrospectively from culture-based records in the Clinical Microbiology department, Sanglah General Hospital during 2012-2014. A. baumanii was isolated from clinical specimens. Identification and antimicrobial susceptibility test were conducted using micro-dilution method (Vitek-2 Compact system). Isolates that resistant to ≥ 3 antibiotic classes were categorized as multi-drug resistant (MDR) A. baumanii.Results: A. baumanii collected from sputum in intensive care unit (ICU) wards were 7.9%, 11.1%, and 7.0%, while the isolates from sputum in non-ICU wards were 13.1%, 15.6%, and 19.9% in 2012, 2013, and 2014, respectively.  There was a reduced susceptibility of A. baumanii to ciprofloxacin, levofloxacin, ceftazidime, aztreonam, imipenem, ampicillin-sulbactam, and piperacillin-tazobactam in ICU ward. Meanwhile, the susceptibility of A. baumanii to Cotrimoxazole remained high in both ICU and non-ICU ward. MDR A. baumanii is found to be resistant to fluoroquinolones, cephalosporins, aztreonam, aminoglycosides, beta-lactamase inhibitors, and carbapenem. Data were analyzed and presented in a descriptive manner.Conclusion: Three years surveillance showed that the susceptibility of A. baumanii to most common antibiotics was decreasing. MDR A. baumanii was found to be resistant to all classes of common antibiotics mostly from ICU ward isolates.